Hierarchical heterostructures based on prickly Ni nanowires/Cu2O nanoparticles with enhanced photocatalytic activity. Issue 17 (20th January 2016) - Li, Xiaolin; Ma, Yujie; Yang, Zhi; Xu, Shusheng; Wei, Liangming; Huang, Da; Wang, Tao; Hu, Nantao; Zhang, Yafei
Abstract : Metal-semiconductor-based photocatalysts show high efficiencies and catalytic activities in the photocatalysis process. Abstract : Metal-semiconductor-based photocatalysts show high efficiencies and catalytic activities in the photocatalysis process. Herein, the magnetic and one-dimensional Ni–Cu2 O heteronanowires have been fabricated via in situ reduction of pre-adsorbed Cu 2+ on the surface of prickly Ni nanowires in an ethanol solution for photocatalysis application. The resultant Ni–Cu2 O heteronanowires show higher photocatalytic ability than pure Cu2 O nanoparticles in the degradation of methyl orange. The enhancement of photocatalytic efficiency can be ascribed to the unique one-dimensional nanostructure and the electron sink effect of Ni nanowires in the heterostructure. It is believed that the low-cost metal Ni is an alternative candidate for substituting the costly metals (Au, Ag and Pt) to improve the photocatalytic ability of semiconductor-based photocatalysts.